A methodology for constructing a formalised dependence of the time of preparation for the re-flight of groups of aircraft on the quantitative and qualitative composition of the aviation engineering service of an aviation unit - Leontiev, Oleksii; Trigub, Yuriy (Social Development and Security, 2024)
Purpose: development of a methodology for constructing a formalised dependence of the time of preparation for the re-flight of a group of aircraft on the quantitative and qualitative composition of the aviation engineering service of an aviation unit based on the use of the results of parametric studies on the means of simulation modelling of the maintenance process. Method: analysis and synthesis, simulation modelling, regression analysis. Findings: the developed mathematical models allow to quickly estimate the required time for preparation for the re-flight of aircraft groups depending on the quantitative and qualitative composition of the aviation engineering service involved in aircraft maintenance. These models provide an opportunity to optimize flight preparation processes, which is critical in the context of modern combat operations. Theoretical implications: the research has contributed to the further development of the theories of simulation modelling and system analysis in the context of organizing aviation engineering support for aviation units, confirming the importance of integrating these approaches to improve the efficiency of aviation units. The work emphasizes the importance of a flexible approach to managing available human resources in the face of changing operational circumstances. Practical implications: the results of the research can be used to optimize the organizational and staffing structure of the aviation engineering service in order to effectively allocate personnel to ensure the preparation of a group of aircraft for re-flight within a regulated specified time. Particularly valuable is the possibility of applying the developed models to different types of aviation units and basing conditions. Value: the value of the research lies in the integration of simulation modelling and analysis of the results of parametric studies with the real conditions of aircraft operation, which leads to the development of more accurate and adaptive methods for planning engineering and aviation support. The importance of the work is determined by its contribution to ensuring greater efficiency and effectiveness of management decisions on planning engineering and aviation support in the context of modern warfare. Future research: the methodology developed in the article for constructing a formalized dependence of the time of preparation for the re-flight of groups of aircraft on the quantitative and qualitative composition of the engineering and aviation service creates prerequisites for developing an improved methodology for synthesizing the rational organizational structure of the engineering and aviation service of aviation units based on the formulation and solution of a mathematical optimization problem.